2005
DOI: 10.1177/0020872805057089
|View full text |Cite
|
Sign up to set email alerts
|

A reanalysis of the IASSW World Census 2000

Abstract: English This reanalysis by region pro.les social work education in 392 programs worldwide. The data veri.ed the .rm base of social work education at universities; demonstrated remarkable consistency across all regions in curriculum structure, pedagogy and content; and con.rmed a strong international perspective through multiple faculty and program exchanges. French Cette nouvelle analyse, par ré gion, trace le profil de l'enseignement en travail social dispensé par 392 programmes à l'é chelle mondiale. Les … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
2
5
1
Order By: Relevance
“…As was found in the earlier surveys (Barretta-Herman, 2005Garber, 2000), the majority of the programs, 65 percent (263 of the 409 reporting) were in public institutions (state-sponsored), an indication of the value of the profession in the eyes of the state. One hundred and twenty-six respondents (27%) described their institution as private, the majority of which described themselves as private/religious.…”
Section: Structure Of Social Work Programssupporting
confidence: 63%
See 1 more Smart Citation
“…As was found in the earlier surveys (Barretta-Herman, 2005Garber, 2000), the majority of the programs, 65 percent (263 of the 409 reporting) were in public institutions (state-sponsored), an indication of the value of the profession in the eyes of the state. One hundred and twenty-six respondents (27%) described their institution as private, the majority of which described themselves as private/religious.…”
Section: Structure Of Social Work Programssupporting
confidence: 63%
“…This stands in sharp contrast with the 2005 Membership Survey, in which 89 percent of the members indicated they had a school mission statement, but significantly higher than the 2000 worldwide census, in which fewer than 35 percent of the respondents indicated they had a mission statement (Barretta-Herman, 2005Garber, 2000). The increase in positive response to the mission statement request may be the result of both the Global Standards, which advises 'All schools should aspire toward the development of a core purpose or mission statement' (IASSW, 2004), and the increase in degree programs reported in the 2010 census.…”
Section: Mission Statementsmentioning
confidence: 74%
“…The re-analysis of the IASSW World Census 2000 profiled social work education worldwide and confirmed that significant similarities exist in the curricula of social work schools across the globe, but with notable regional differences. It also confirmed cross-national exchange relationships among the faculty (Barretta-Herman, 2005), which is one of the themes in ISW.…”
Section: Review Of Curricular Research In Social Worksupporting
confidence: 55%
“…In this regard, a few of the published articles in the literature used quantitative techniques. The first was an IASSW survey in response to the absence of a worldwide database for educational programs in social services (Barretta-Herman, 2005). The re-analysis of the IASSW World Census 2000 profiled social work education worldwide and confirmed that significant similarities exist in the curricula of social work schools across the globe, but with notable regional differences.…”
Section: Review Of Curricular Research In Social Workmentioning
confidence: 99%
“…These member schools that responded seemed to be decisively more established than the schools responding to the 2000 world census ( Barretta-Herman, 2005). Over 33 percent of the 127 schools that responded to this question were started before 1970, compared with only 14 percent in the 2000 world census.…”
Section: The Respondentsmentioning
confidence: 99%